The role of ethnic politics in promoting democratic governance: a case study of Malaysia - Shukri, Syaza Farhana Mohamad (2015)
Introduction The demographic of most Asian countries is made up of multiple ethnicities or religious groups, a fact that is not lost on those who believe that homogeneity is an important precondition for democracy. Asia is unique because of its vast territory and the peoples inhabiting it, making the project of nation building challenging. The national boundaries that were demarcated by exiting colonial masters, unfortunately, did not take into account the ethnic, religious, or even linguistic makeup of countries. As a result, the democratic prospects of these heterogeneous countries were believed to be doomed from the outset. However, as this paper will argue by using Malaysia as a case study, politics based on social diversity do not necessarily inhibit the development of democracy with the right leadership and institutions in place. Compared to other multi-ethnic societies such as Sri Lanka and Northern Ireland, Malaysia has been more successful at maintaining democratic governance. Although diversity does not guarantee stability or peace in a democratic nation, it is not impossible for it to help consolidate a democracy where there already is one. This paper applies qualitative methodology in developing the arguments, mainly using process tracing and counterfactual methodologies to discover the intervening variables responsible for the maintenance of democratic governance in Malaysia. Evidence such as power sharing, strong leadership, and institutional moderation confirm the validity of the two methods applied.